Intracontinental evolution of the southern Central Asian Orogenic Belt: Evidence from Late Triassic nappe structure in the northern Alxa region, NW China. (March 2023) - Yu, Wei; Shao, Zhaogang; Niu, Manlan; Su, He; Zhang, Yiping; Wang, Yongchao
Graphical abstract: Highlights: Field mapping indicated the geometry of nappe structure in the northern Alxa region, NW China. The crustal shortening of the southern CAOB was established during the Late Triassic. Two large-scale strike-slip systems dominated the Late Triassic tectonic framework of the southern CAOB. Abstract: The Central Asian Orogenic Belt (CAOB) experienced multistage intracontinental deformation during the Mesozoic and Cenozoic. Recent studies have shown that a large-scale nappe structure developed in the northern Alxa region. Here, we present new field investigations, structural analysis, and a new balanced cross-section in order to better constrain its geometries, displacement and activity time. Three nappe stacks with distinctive lithostratigraphic assemblies, structural characteristics and displacement were recognized: (1) the structural highest China-Mongolia boundary nappe preserving as klippen has a minimum displacement of ∼ 65 km; (2) the Yagan thrust sheet is dominated by an E–W-trending syncline and has a minimum displacement of ∼ 30 km; and (3) the structural lowest Gashunzhadegai thrust sheet is characterized by S-vergent folds and imbricated faults and has a minimum displacement of ∼ 14 km (30 %). The youngest strata involved in the nappe structure and the cross-cutting relationships indicated that the nappe structure formed during the Late Triassic (230–215 Ma). Regionally, it occurred later than the final closure of the Paleo-Asian Ocean and marked the beginning of the intracontinental evolution of the southern CAOB. Integrating previous structural, thermochronological and sedimentological data with our studies, we suggested that the Late Triassic tectonic framework of the middle segment of the southern CAOB was dominated by two large-scale en echelon strike-slip systems. In addition, the driving force for the Late Triassic intracontinental deformation was most likely to be the collision of the Bayan Har Terrane and Yangtz Craton with the Eurasian continent.